Correlation between radiculalgia and counts of T lymphocyte subsets in the peripheral blood of patients with lumbar disc herniation - Tian, Peng (Orthop Surg, 2009)
Objective:  To determine the correlation between the degree of radiculalgia and counts of T lymphocyte subsets in the peripheral blood of patients with lumbar disc herniation. Methods:  Forty‐nine patients with lumbar disc herniation (group A) were divided into three subgroups according to Visual Analogue Scale (VAS) pain scores (group A(1): n= 12, VAS 0–4.0; A(2): n= 24, VAS 4.1–7.0; A(3): n= 13, VAS 7.1–10.0. Twenty health blood donors who volunteered to be involved in the study comprised the control group (group B). Peripheral blood counts of various T lymphocyte subsets were measured in each group. Results:  (i) The counts of CD4+ T and CD4+/CD8+ lymphocytes were higher in group A than in group B, and the difference between the two groups was statistically significant (P < 0.05). There were also statistically significant differences between group A and group B in the counts of CD3+ and CD8+ T lymphocytes (P < 0.05); (ii) There was no correlation between the VAS scores and the counts of CD3+ T lymphocytes (r= 0.194, P > 0.05). A strong significant correlation was observed between the VAS scores and counts of CD4+ T lymphocytes (r= 0.542, P < 0.05), CD4+/CD8+ (r= 0.468, P < 0.05), which increased with increasing VAS scores in the three subgroups of group A (P < 0.05). However there was a significant negative linear correlation between CD8+ T lymphocyte counts and pain scores (r=−0.462, P < 0.05). Conclusion:  Our results suggest that changes in T lymphocyte subsets in peripheral blood take place after prolapse of lumbar intervertebral discs. The current results may provide support for involvement of immunologic mechanisms in low back pain secondary to herniation of the lumbar disc. T lymphocytes may play an important role in the development of symptoms in patients with lumbar intervertebral disc herniation.